Sex differences in inflammation correlated with estrogen and estrogen receptor-β levels in azoxymethane/dextran sodium sulfate-induced colitis-associated colorectal cancer mice - Seoyoung Jang; Hyejin Han; Yeonsoo Oh; Yuri Kim (Heliyon, 2024)
Colorectal cancer (CRC) is a type of cancer that develops in the colon or rectum and is the second leading cause of cancer-related death worldwide. Several epidemiology studies have identified a significant sexual dimorphism in CRC, with women exhibiting a lower incidence rate and delayed onset compared to men. This study aims to investigate the sexual dimorphism in the inflammatory response in colitis-associated CRC and its relationship with estrogen and estrogen receptors. An azoxymethane (AOM)/dextran sodium sulfate (DSS) mouse model was used to induce colitis-associated CRC. Five-week-old male and female mice were randomly assigned into either the control group or the AOM/DSS CRC group, with 10 mice in each group. Colitis-associated CRC was induced by injecting AOM (10 mg/kg) and administering two-cycles of DSS treatment in the drinking water. The results revealed a significant decrease in colon length exclusively in the female group, indicating more severe colonic inflammation (P < 0.01). A significant interaction was identified between sex and AOM/DSS treatment in the female AOM/DSS group, with higher visceral fat weight compared to their male counterparts (P < 0.05). The female AOM/DSS group also exhibited elevated production of M1 macrophage-related pro-inflammatory cytokines, suggesting increased tumor-associated macrophage activity. Surprisingly, the male AOM/DSS group showed a marked increase in serum estradiol levels, while the female AOM/DSS group exhibited a decrease compared to the normal control group. Additionally, a notable upregulation of both estrogen receptor α and estrogen receptor β expression was observed in the colon tissues of the AOM/DSS groups compared to the normal control groups, with estrogen receptor β expression being particularly pronounced in females. Taken together, our findings suggest that a decline in endogenous estrogen and increased estrogen receptors potentially contribute to the pro-inflammatory response in early CRC by augmenting cytokine expressions associated with M1 macrophage polarization in females.